Glycan Assembly Strategy: From Concept to Application. Issue 11 (9th September 2021) - Liu, Mingli; Qin, Xianjin; Ye, Xin‐Shan
Abstract: Glycans have been hot topics in recent years due to their exhibition of numerous biological activities. However, the heterogeneity of their natural source and the complexity of their chemical synthesis impede the progress in their biological research. Thus, the development of glycan assembly strategies to acquire plenty of structurally well‐defined glycans is an important issue in carbohydrate chemistry. In this review, the latest advances in glycan assembly strategies from concepts to their applications in carbohydrate synthesis, including chemical and enzymatic/chemo‐enzymatic approaches, as well as solution‐phase and solid‐phase/tag‐assisted synthesis, are summarized. Furthermore, the automated glycan assembly techniques are also outlined. Abstract : The latest advances in glycan assembly strategies from concepts to their applications in carbohydrate synthesis, including chemical and enzymatic/chemo‐enzymatic approaches, as well as solution‐phase and solid‐phase/tag‐assisted synthesis, are summarized. Furthermore, the automated glycan assembly techniques are also outlined.